ANALISIS PENGARUH BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN DI CLOVIA RESTAURANT, HOTEL MERCURE JAKARTA SABANG - Claudia, Angel; Sofiani, Sofiani (Jurnal Ilmiah Global Education, 2023)
This research discusses the influence of brand awareness on purchasing decisions. It is important to pay attention to increasing brand awareness so that more consumers know a brand because the less brand is known to the public, the more difficult it is to increase purchases. This research aims to determine the influence of brand impression, brand recall, purchase decision, brand recognition, brand reach, consumption brand on awareness brand influence on purchase decisions, brand awareness overall influence on purchasing decisions, and find out level of brand awareness on Clovia Restaurant, Mercure Jakarta Sabang Hotel. Using a quantitative approach by distributing questionnaires to 393 respondents with certain criteria. Population in this study was focused on respondents who knew Clovia Restaurant.  The result of this research, there is a significant influence on brand impressions, brand recall, purchase decisions, brand recognition, brand reach, and brand consumption on brand awareness on purchasing decisions. Brand awareness shows a significant of 0.000 < 0.05 which means that there is a simultaneous positive, significant influence on purchasing decisions at Clovia Restaurant. Also 85.4% brand awareness influence on purchasing decisions. Clovia Restaurant based on the existing level to the results of the questionnaire is at the level Brand Recall.